Razonamientos por la paridad - Camacho De la O, Ana Lorena Autora 23277; Instituto Nacional de las Mujeres (Costa Rica) 23214; Blanco Lizano, Randall Autor 23520 (San José, CR, Instituto Nacional de las Mujeres (Costa Rica), 2004)
1